PENGARUH KESADARAN POLITIK TERHADAP PASRTISIPASI POLITIK MASYARAKAT KECAMATAN TENAYAN RAYA DALAM PEMILIHAN UMUM WALIKOTA PEKANBARU TAHUN 2017 - ', Mernasusanti; Erlinda, Sri; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: One manifestation of political consciousness is political participation in the election of the mayor. Political participation based on political consciousness will encourage people to exercise their right to vote rationally and in accordance with the aspirations of the people. But in reality, the level of voter participation in the election mayor of Pekanbaru in 2017 is still lacking. Percentage of voters' participation in sub district Tenayan Raya only reached 43.72%, which means there are still many voters who did not participate that reached 56.28%. This study aims to explain the effect of political awareness on political participation. This study uses quantitative descriptive by spreading questionnaires to 100 respondents in four urban villages in Tenayan Raya sub district, then the data is analyzed by using logistic regression. Based on the result of research, it can be concluded that there is a significant influence between political awareness on political participation because the value of p value Chi-Square 13,105 > Chi-Square table 3,841. In the Pseudo R Square table of 16.4% political awareness contribution to political participation, in other words 83.6% other factors from outside the model that explain the dependent variable. Based on the analysis of political awareness data of Tenayan Raya sub-district is low down to 68%, while the political participation of Tenayan Raya community in the election of mayor of Pekanbaru is also categorized as low by 94%.Keywords: Political Awareness, Political Participation